OPTIMALISASI PERAN MUDHARABAH SEBAGAI SALAH SATU AKAD KERJASAMA DALAM PENGEMBANGAN EKONOMI SYARIâAH - Nurhasanah, Neneng (Syiar Hukum, 2010)
Mudharabah is a permissible commercial agreement in Islam and it contains great benefits for human beings. Mudharabah role in Shariah economic development is very important in improving the welfare and empowering the economic of people. Mudharabah will correlate the people with surplus of fouds to the people with lack of fouds for reaching the human welfare (al falah) through organizing the natural resources which is based on cooperation and participation. However, Mudharabah is not implemented optimally yet, there are several obstacles in implementing it, Therefore, there is a need a comprehensive measurement to socialized the utility of mudharabah to the people through education and dissemination, and it has to be done by certain institutions such as, shariah financial institution, Association of Muslim Scholars (MUI), ademicians and also from prominent figures in the society.